Prevalence and Associated Factors of Emotional and Behavioural Difficulties during COVID-19 Pandemic in Children with Neurodevelopmental Disorders - Jacqueline Nonweiler; Fiona Rattray; Jennifer Baulcomb; Francesca Happé; Michael Absoud (MDPI AG, 2020)
Children and young people (CYP) with neurodevelopmental disorders (NDDs) may be particularly vulnerable to adverse mental health effects due to the COVID-19 pandemic. We conducted a cross-sectional U.K. parent-reported study from 2nd April-2nd June 2020, using the Strengths and Difficulties Questionnaire. CYP with NDDs (n = 371), compared to neurotypical controls, had a higher prevalence of emotional symptoms (42% vs. 15%) and conduct problems (28% vs. 9%), and fewer prosocial behaviours (54% vs. 22%). All groups had worse emotional symptoms than pre-COVID groups, and those with attention-deficit/hyperactivity disorder showed inflated conduct problems, while those with autism spectrum disorder exhibited decreased prosocial behaviours. Females with ASD had higher emotional symptoms compared to males. CYP with NDDs, and those without, showed higher levels of parent-reported mental health problems than comparable cohorts pre-COVID-19.